Penanganan Rembesan dan Perkuatan Tanah Menggunakan Metode Insitu Test (Pressure Meter Test) Studi Kasus : Proyek Bendungan Margatiga - Nora Anggraini; Endro Prasetyo Wahono; Dyah Indriana Kusumastuti (Jurnal Sipil Terapan, 2024)
The bearing capacity of the soil is the support of the foundation, where the foundation transmits the loads derived from the weight of the building itself and the loads acting on the building to the surrounding soil. The purpose of this paper is to determine the handling of seepage and soil reinforcement needed in the case study of the Margatiga Dam Project, East Lampung. Based on the results of geological investigations, the Margatiga Dam is composed of a quarter-aged rock layer with a fragment composition of fine sand - gravel, with a soft - hard hardness level and the need for foundation repair. Based on the lithological conditions of the Margatiga Dam Extraction Gate foundation and the Spillway building which are composed of relatively deep and quite porous alluvial sand deposits, this causes the curtain grouting results to be ineffective, therefore it is necessary to change the seepage control design from the Grouting Curtain to the boundary wall. Based on the simulation check in Plaxis Software for Seepage and Excavation Staging, processing was carried out using Secant Pile and Soldier Pile with a depth of 30 meters with a stretch of 140 m and overlapping with Curtain Grouting of Embankment Dam on the left side and 5 m right side. Field PMT results showed that the maximum stress of the rock layer under the spillway foundation was 0.016 MPa and 0.630 MPa.